2018
DOI: 10.1007/s10072-018-3506-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal administration of Nusinersen in type 1 SMA: successful psychological program in a single Italian center

Abstract: Nusinersen is the first approved drug to treat spinal muscular atrophy (SMA). Its periodic intrathecal delivery may cause psychological burden in infants and in their parents. We report our experience during expanded access program (EAP) for type 1 SMA in a single Italian center. Because of the occurrence of stress emotional states, anxious reactions and fear before, during, and after lumbar puncture (LP), a specific psychological intervention was implemented based on regulation of emotions, anticipatory expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…CarerQoL baseline median score = 4 (SD = 1.4) versus 6-month median score = 8 (SD = 1.3, p < 0.001). La Foresta et al [ 34 ] Italy Longitudinal study, 3 time points (before 1st and 4th lumbar puncture (LP)), self-report paper–pencil questionnaire December 2016 (start), clinic N = 14 Sex: 93% female Age: NR Family status: NR Employment: NR Comparison group: different time points (pre-post) N = 16 Sex: 69% male Age: 50% between 1 and 10 (range = 0.16–14) SMA subtypes: I = 100% Medication: nusinersen = 100% Comparison group: different time points (pre-post) State anxiety (State-Trait Anxiety Inventory for adults, STAI) State anxiety : 2 h before the 1st lumbar puncture (LP), mild anxiety levels were found in caregivers. Preoperative anxiety had increased significantly ( p < 0.001) at the 4th LP, but significantly decreased after implementation of a self-developed psychological intervention at the 5th LP ( p < 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CarerQoL baseline median score = 4 (SD = 1.4) versus 6-month median score = 8 (SD = 1.3, p < 0.001). La Foresta et al [ 34 ] Italy Longitudinal study, 3 time points (before 1st and 4th lumbar puncture (LP)), self-report paper–pencil questionnaire December 2016 (start), clinic N = 14 Sex: 93% female Age: NR Family status: NR Employment: NR Comparison group: different time points (pre-post) N = 16 Sex: 69% male Age: 50% between 1 and 10 (range = 0.16–14) SMA subtypes: I = 100% Medication: nusinersen = 100% Comparison group: different time points (pre-post) State anxiety (State-Trait Anxiety Inventory for adults, STAI) State anxiety : 2 h before the 1st lumbar puncture (LP), mild anxiety levels were found in caregivers. Preoperative anxiety had increased significantly ( p < 0.001) at the 4th LP, but significantly decreased after implementation of a self-developed psychological intervention at the 5th LP ( p < 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies focused on affected families or patients and parents equally [ 29 , 31 , 37 40 ]. Five studies focused primarily on caregiver outcomes [ 15 , 32 , 33 , 36 , 41 ] and four studies assessed patients’ perspectives but, additionally, reported outcomes for parents [ 16 , 17 , 30 , 34 ]. The majority of studies were cross-sectional, only three studies used a longitudinal design with two to three time points [ 34 , 38 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations